PEMAHAMAN DAN PRAKTIK KOMUNIKASI POLITIK AKTIVIS GENERASI Z MENJELANG PILKADA 2024 DI KOTA PALEMBANG - Maharani Hardian, Siti; Muhaimin, Ahmad; Setiawan, M.Arif (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study explores the understanding and practice of political communication among Generation Z activists ahead of the 2024 regional election in Palembang using a qualitative approach. Data were obtained through in-depth interviews with Generation Z activists and relevant literature analysis. The theory of symbolic interactionism is used to understand how political understanding is formed through communication and social interaction within the context of local politics. Generation Z activists in Palembang play a crucial role in disseminating political information, particularly to young voters, through community discussions and social media. The findings show that activists actively engage in various forms of political activities such as discussions, policy advocacy campaigns, and election monitoring to ensure a transparent and fair electoral process. Social media serves as their primary platform for spreading relevant political information and raising public awareness. However, activists also face challenges related to misinformation and disinformation on social media, which can negatively influence public opinion. Through social interactions within communities and organizations, these activists construct collective meanings regarding social and political issues that are highly relevant to their lives. In conclusion, the involvement of Generation Z activists in Palembang’s 2024 regional election reflects their commitment to political and social change. Therefore, strengthening social media literacy, improving political education, and ensuring more transparent election monitoring are essential to empower young generations to continue acting as agents of change for societal progress. These activists play a critical role in supporting democratic sustainability and social advancement.